1982
DOI: 10.1002/ardp.19823150910
|View full text |Cite
|
Sign up to set email alerts
|

Reaktionen von 2‐Benzoylacetamidin mit 1,3‐Dicarbonylverbindungen

Abstract: 2‐Benzoylacetamidin (1) kondensiert mit Malondialdehyd‐Derivaten und 1,3‐Ketoaldehyden zu 2‐Amino‐3‐pyridyl‐phenylketonen. Aus 1 und 1,3‐Diketonen entstehen 2‐Phenacylpyrimidine, die in Lösung als chelatisierte Enole vorliegen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1983
1983
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 10 publications
(1 reference statement)
0
1
0
Order By: Relevance
“…243 In the case of 2-benzoylacetamidate and 2-benzoylacetamidine in ethanolic solution, the chelated enolimine forms, HOsC(Ph)dCHsC(OEt)dNH and HOsC(Ph)dCHs C(NH 2 )dNH, respectively, are preferred instead. 244 Semiempirical and ab initio studies, 245 enriched recently by the detailed theoretical conformational analysis of Buemi et al,246 showed that the chelated enaminone tautomer is the most stable form for unsubstituted -aminoacrolein although the O-H‚‚ ‚N bridge (RAHB) in the other chelated enolimine tautomer, which is less stable by about 7 kcal mol -1 at the B3LYP/6-31G** level, seems to be the strongest bridge. The strength of the O-H‚‚‚N bridge is slightly greater than that of the O-H‚‚‚O bridge in malondialdehyde.…”
Section: Estimated For Enol Tautomers and Transition States (Ts) For mentioning
confidence: 98%
“…243 In the case of 2-benzoylacetamidate and 2-benzoylacetamidine in ethanolic solution, the chelated enolimine forms, HOsC(Ph)dCHsC(OEt)dNH and HOsC(Ph)dCHs C(NH 2 )dNH, respectively, are preferred instead. 244 Semiempirical and ab initio studies, 245 enriched recently by the detailed theoretical conformational analysis of Buemi et al,246 showed that the chelated enaminone tautomer is the most stable form for unsubstituted -aminoacrolein although the O-H‚‚ ‚N bridge (RAHB) in the other chelated enolimine tautomer, which is less stable by about 7 kcal mol -1 at the B3LYP/6-31G** level, seems to be the strongest bridge. The strength of the O-H‚‚‚N bridge is slightly greater than that of the O-H‚‚‚O bridge in malondialdehyde.…”
Section: Estimated For Enol Tautomers and Transition States (Ts) For mentioning
confidence: 98%